Enhancing effects of activated carbon supported nano zero-valent iron on anaerobic digestion of phenol-containing organic wastewater. (15th August 2019) - Dong, Duo; Wang, Ruikun; Geng, Pengfei; Li, Chunxi; Zhao, Zhenghui
Abstract: Activated carbon supported nano zero-valent iron material (NZVI/AC) was prepared and added to an anaerobic digestion tank to reduce the toxicity inhibition of phenols and increase the methane yield of phenol-containing organic wastewater (POW). The anaerobic digestion (AD) characteristics, including conversion rate of organic substances, removal rate of phenol, and methane yield of POW with different concentrations of phenol were studied, and moreover, the enhancing effects of NZVI/AC on the AD of POW were focused. When the concentration of phenol was below 500 mg/L, the methane yield from AD of POW was 387.5 mL, which was 10.71% higher than that from control organic water without phenol, however, phenol concentrations greater than 1000 mg/L severely inhibited AD, and methane yield was only 50% of the control sample. Indicating that anaerobic microorganisms had a certain degree of tolerance to phenol, and low concentration of phenol could promote AD of organic water although the phenol with high concentration showed severe inhibition. The methane yield increased due to the probable conversion of phenol to methane by microbial actions. In the AD of POW with 500 mg/L phenol, the conversion rate of organic substances increased from 37.49% (control group without any accelerant) to 66.56% after adding NZVI/AC. The removal rate of phenol also increased from 39.03% to 81.32%. Cumulative methane yield increased by 145.5%–810 mL compared with the control group. The AC carrier in NZVI/AC exerted a good adsorption effect on phenols, reducing the concentration of phenols in the solution and thus minimizing their toxic effects on microbial activity. The NZVI loaded on AC particles strengthened the electron transfer between methanogens by its good electrical conductivity, and then promoted the AD performance of organic matter. Furthermore, NZVI exerted a micro-electrolytic effect on phenolic substances, which could increase the removal rate of phenol. Therefore, NZVI/AC could be used as an efficient accelerant for the AD of POW to enhance the AD process. Graphical abstract: Image 1 Highlights: Phenol concentrations higher than 1000 mg/L severely inhibited AD. NZVI/AC could reduce the inhibition of phenols and strengthen fermentation. RRphen was proportional to the removal rate of COD and the MYt during AD. NZVI/AC adsorbed phenol and improved the survival environment of the methanogens. NZVI/AC exhibited a stronger effect in promoting the methanation than AC.